MORPHOFUNCTIONAL AND CLINICAL SIGNIFICANCE OF APUD CELLS VISUALIZED IN SOME TISSUES OF HUMAN ORGANS - Sherstyuk О.О.; Ustenko, R.L.; Tykhonova О.О.; Tarasenko, J.A.; Katsenko, A.L.; Lytovka, V.V.; Korchan N.О. (World of Medicine and Biology, 2023)
Different organs and systems of the human body contain diffusely located and so-called APUD cells. There are about 40 of their varieties for today. The article provides modern information about the localization, structural features and role of this group of cells, as well as their clinical significance. Archival data of biopsies of palatine, labial, lacrimal glands, stomach, gums, and prostate gland of a person in the condition of their normal intravital functioning were studied. Some morphological and functional characteristics of APUD cells from the palatal salivary gland, interdental gingival papilla, gastric pyloric gland, and human prostate gland have been reported. The study of APUD cells retains important clinical significance because it is the basis for the treatment of apudomas.